Managing development in small island states : an inter-regional training and capacity-building project (International Training Centre for the ILO TurinIT, 1996)
Presents the proposal for a project which seeks to enhance the capacity of small island states to provide and manage sustainable development in key areas of economic and environmental concern, by strengthening the capability of regional and national training institutions to design and deliver short cycle HRD programmes for policy makers, planners and practioners.
DC